On the validity of use of physical equations and principles in the socio-economic field and on the predictability of socio-economic system dynamics - Andreev, Vsevolod V V (Nonlinear Analysis: Modelling and Control, 2015)
Usually, the various empirical and semi-empirical equations and mathematical models are used to study the dynamics of socio-economic systems. In this case, there are very often questions related to the validity of application of such equations and models. In this paper, it is shown that the dynamics of socio-economic systems can be described by mathematical equations analogous to the motion equations that are well known in physics (particularly in classical mechanics). In this connection, it is possible to say that the predictability of the dynamics of a socio-economic system is described by the motion equations (i.e., Newton's equations) to the same degree that these equations predict the dynamics of the physical system. Such models allow us to determine the trends of development in the dynamics of socio-economic systems. The importance of this investigation in using adequate mathematical models is that they allow us to notice those or other adverse trends in the socio-economic systems, therefore, ensuring timely optimal management decisions.
Keywords: motion equations; system identification; making optimal management decisions; mathematical models of socio-economic systems; predator–prey models; identification of tendencies in the socio-economic systems